2010
DOI: 10.1111/j.1365-2524.2010.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and behaviours related to herbal remedies: a cross-sectional epidemiological study in adults in Middle Anatolia, Turkey

Abstract: The use of herbal remedies is common in Turkey. This study aimed to define the patterns of herbal remedy use among subjects aged 18 or above and to describe factors associated with use of herbal remedies. A cross-sectional study was conducted with a multistage sampling method between September 2007 and April 2008. A total of 3876 adults participated (98.1% response rate), and 1518 (39.2%) admitted using herbal remedies (95% CI 37.6-40.7%). Univariate analyses showed that compared with non-users, herbal users w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
47
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 17 publications
12
47
3
Order By: Relevance
“…Our findings corroborate those of prior studies showing that higher education levels and being of older age are associated with NHP use as compared to lower education and young age [5,9,16,[28][29][30]. Unlike the majority of previous research which shows more females use CAM than males [5,[12][13][14][15], we find no significant difference between gender and NHP use. The exception to this result was the observation that male students use chamomile less than female students.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings corroborate those of prior studies showing that higher education levels and being of older age are associated with NHP use as compared to lower education and young age [5,9,16,[28][29][30]. Unlike the majority of previous research which shows more females use CAM than males [5,[12][13][14][15], we find no significant difference between gender and NHP use. The exception to this result was the observation that male students use chamomile less than female students.…”
Section: Discussionsupporting
confidence: 89%
“…11 Similarly, poor communication between patients and health care professionals regarding herbal product use was also reported by other studies. 14,19,20 Respondents using herbal medicines without informing the treating physician may have to bear the brunt of serious clinical implications due to the possible herb-drug interactions. It has been found that herbal products interact or interfere with the normal pharmacology of some drugs with potentially fatal consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we focus on the herbal medication that is not prescribed by physicians. A cross-sectional study in Turkey showed that the prevalence of herbal remedies was 39.2%, and lime, mint, rosehip, and lemon are the most commonly used herbs ( 59 ). A study in Northwest reported that although there was a decrease in the usage of some traditional medical plants, the decreasing process was not homogeneous ( 60 ).…”
Section: Prevalence Of Self-treatmentmentioning
confidence: 99%